Urinary cadmium concentration and the risk of ischemic stroke. (24th July 2018) - Chen, Cheng; Xun, Pengcheng; Tsinovoi, Cari; McClure, Leslie A.; Brockman, John; MacDonald, Leslie; Cushman, Mary; Cai, Jianwen; Kamendulis, Lisa; Mackey, Jason; He, Ka
Abstract : Objectives: To examine the association between urinary cadmium levels and the incidence of ischemic stroke and to explore possible effect modifications. Methods: A case-cohort study was designed nested in the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study, including 680 adjudicated incident cases of ischemic stroke and 2, 540 participants in a randomly selected subcohort. Urinary creatinine–corrected cadmium concentration was measured at baseline. Multivariable-adjusted hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs) were estimated with the Barlow weighting method for the Cox proportional hazards regression model. Results: The median urinary cadmium concentration was 0.42 (interquartile range 0.27–0.68) μg/g creatinine. After adjustment for potential confounders, urinary cadmium was associated with increased incidence of ischemic stroke (quintile 5 vs quintile 1: HR 1.50, 95% CI 1.01–2.22, p for trend = 0.02). The observed association was more pronounced among participants in the lowest serum zinc tertile (tertile 3 vs tertile 1: HR 1.82, 95% CI 1.06–3.11, p for trend = 0.004, p for interaction = 0.05) but was attenuated and became nonsignificant among never smokers (tertile 3 vs tertile 1: never smokers: HR 1.27, 95% CI 0.80–2.03, p for trend = 0.29; ever smokers: HR 1.60, 95% CI 1.06–2.43, p for trend = 0.07, p for interaction = 0.51). Conclusions: Findings from this study suggest that cadmium exposure may be an independent risk factor for ischemic stroke in the US general population. Never smoking and maintaining a high serum zinc level may ameliorate the potential adverse effects of cadmium exposure.